2020
DOI: 10.5194/dwes-13-15-2020
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption and desorption studies of <i>Delonix regia</i> pods and leaves: removal and recovery of Ni(II) and Cu(II) ions from aqueous solution

Abstract: Abstract. In this study, the adsorption of Ni(II) and Cu(II) ions from aqueous solutions by powdered Delonix regia pods and leaves was investigated using batch adsorption techniques. The effects of operating conditions such as pH, contact time, adsorbent dosage, metal ion concentration and the presence of sodium ions interfering with the sorption process were investigated. The results obtained showed that equilibrium sorption was attained within 30 min of interaction, and an increase in the initial concentrati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…The percentage removal increased marginally from 91.81 to 99.30% as the BSSP dosage increased to 0.10 from 0.05 g/100 mL (Figure ). This may be attributed to the rise in the number of active sites that are currently available as the BSSP dosage increased, which in turn increased the surface area, resulting in a higher percentage removal . Also, the percentage removal decreased slightly as the dosage was further increased from 0.10 to 0.25 g (99.30–92.61%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The percentage removal increased marginally from 91.81 to 99.30% as the BSSP dosage increased to 0.10 from 0.05 g/100 mL (Figure ). This may be attributed to the rise in the number of active sites that are currently available as the BSSP dosage increased, which in turn increased the surface area, resulting in a higher percentage removal . Also, the percentage removal decreased slightly as the dosage was further increased from 0.10 to 0.25 g (99.30–92.61%).…”
Section: Resultsmentioning
confidence: 99%
“…This may be attributed to the rise in the number of active sites that are currently available as the BSSP dosage increased, which in turn increased the surface area, resulting in a higher percentage removal. 44 Also, the percentage removal decreased slightly as the dosage was further increased from 0.10 to 0.25 g (99.30− 92.61%). This could be due to active site overlapping caused by excess BSSP particles.…”
Section: Batch Adsorption and Effects Of Operational Parameters 321 E...mentioning
confidence: 97%
“…The R 2 value is highly significant. Based on 𝑅 2 values of these isotherm models, it was concluded that the Freundlich, Jovanovich, Dubinin-Radushkevich, Temkin isotherms, and Langmuir 1,2 were better models than the Harkin-Jura model, however, Harkin-Jura constant, A values greater than 1, suggest better curve fitting, and the adsorption is favorable for Harkin-Jura isotherm (12,21).…”
Section: Harkin-jura Modelmentioning
confidence: 99%
“…It thus, becomes an issue of paramount importance to treat dye containing wastewater and effluents from industrial processes where dyes are used before they are discharged. Conventionally, treatments such as chemical precipitation, flocculation, electro-floatation, microbial biodegradation, ion-exchange, ozonation and membrane filtration, adsorption and advanced treatment techniques [3][4], have been used to treat and remove dyes from wastewaters but not without limitations or disadvantages in terms of energy requirement such as reagent needed and power supply, sludges that require further treatment before it is suitable for discharge [2,5]. Adsorption, seems to be the most promising among these methods since its design is simple to adapt and modify, has been efficiently applied to many wastewaters systems without the generation of toxic sludge [6], there's easy recovery of adsorbate, possibility of tuning adsorbent properties, high regeneration capacity and involves low cost in comparison with other used techniques [7].…”
Section: Introductionmentioning
confidence: 99%